FORMULATION OF NEW GAS HYDRATE INHIBITOR FOR DEW POINT CONTROL UNIT SYSTEM: THEORETICAL STUDY - TEO, MELVRICK TWAN CHUAN (IRC, 2019)
Gas hydrate is a solid ice alike compound in its appearance formed when there are hydrocarbons such as methane, propane, butane and isobutane that mixed with water content in high pressure and low temperature condition (Hammerschmidt, 1934). The formation of hydrates is depending of the pressure, temperature and the presence of water in hydrocarbons. This problem usually happens in offshore pipelines where the condition of hydrate formation is met which are low temperature and high- pressure during transportation of hydrocarbons from offshore to onshore. Gas hydrate inhibitor is an invention relates to a procedure where it prevents or slowing down the gas hydration nucleation process to occur. (Tieu et al, 2002) .